Implementing a regional School Health Research Network in England to improve adolescent health and well-being, a qualitative process evaluation - Emily Widnall; Lorna Hatch; Patricia N Albers; Georgina Hopkins; Judi Kidger; Frank de Vocht; Eileen Kaner; Esther MF van Sluijs; Hannah Fairbrother; Russell Jago; Rona Campbell (BMC, 2023)
Abstract Background There is an increased need for prevention and early intervention surrounding young people's health and well-being. Schools offer a pivotal setting for this with evidence suggesting that focusing on health within schools improves educational attainment. One promising approach is the creation of School Health Research Networks which exist in Wales and Scotland, but are yet to be developed and evaluated in England. Methods This qualitative process evaluation aimed to identify the main barriers and facilitators to implementing a pilot School Health Research Network in the South West of England (SW-SHRN). Semi-structured interviews were conducted with school staff, local authority members, and other key stakeholders. Interview data were analysed using the 7-stage framework analysis approach. Results Four main themes were identified from the data: (1) 'Key barriers to SW-SHRN' (competing priorities of academic attainment and well-being, schools feeling overwhelmed with surveys and lack of school time and resource); (2) 'Key facilitators to SW-SHRN: providing evidence-based support to schools' (improved knowledge to facilitate change, feedback reports and benchmarking and data to inform interventions); (3) 'Effective dissemination of findings' (interpretation and implementation, embedding findings with existing evidence and policy, preferences for an online platform as well personalised communication and the importance of involving young people and families); and (4) 'Longer-term facilitators: ensuring sustainability' (keeping schools engaged, the use of repeat surveys to evaluate impact, informing school inspection frameworks and expanding reach of the network). Conclusion This study identifies several barriers to be addressed and facilitators to be enhanced in order to achieve successful implementation of School Health Research Networks in England which include providing a unique offering to schools that is not too burdensome, supporting schools to take meaningful action with their data and to work closely with existing organisations, services and providers to become meaningfully embedded in the system.